Secular Stagnation? Growth, Asset Returns and Welfare in the Next Decades - Alexander Ludwig; Christian Geppert; Raphael Abiry (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Ongoing demographic change will lead to a relative scarcity of raw labor to the effect that output growth will be decreasing in the next decades, a secular stagnation. As physical capital will be relatively abundant, this decrease of output will be accompanied by reductions of asset returns. We quantify these effects for the US economy by developing an overlapping generations model in which we explicitly model risky and risk-free asset returns. This enables us to predict how the natural interest rate is affected by the demography induced secular stagnation. Without adjustments of human capital, risky returns decrease until 2035 by about 0.7 percentage point, and the risk-free rate by about one percentage point, leading to severe welfare losses for asset rich households. Endogenous human capital adjustments strongly mitigate these effects. We conclude that human capital policies will be crucial in the context of labor shortages.
Keywords: E17; C68; G12; 330